Development of Mathematics Digital Creative (Magic) Book for Elementary School - Faizah, Hanim; Sugandi, Eko; Susiloningsih, Wahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
The digitalization of education is a logical consequence of changing times. No one could have predicted that technology would be adopted so quickly by industry and society. The Covid-19 pandemic has cause students, teachers and schools to carry out teaching and learning activities by relying on digital technology. The use of e-book is becoming a trend because it is more environmentally friendly and more economical. The purpose of this research is to develop a 4C-oriented Mathematics Digital Creative (Magic) Book for elementary school students to determine the development process, feasibility, and effectiveness of its use. The results of the research show that the users gave a positive rating for the MAGIC Book. The use of digital modules provides benefits in learning, especially in online learning.